Overview of ultrasonic shot peening. (2nd September 2017) - Yin, Fei; Rakita, Milan; Hu, Shan; Han, Qingyou
ABSTRACT: Ultrasonic shot peening (USP) is acknowledged as an effective surface treatment method to enhance the mechanical performance of materials by inducing compressive residual stress in solid metals and alloys. This article overviews recent researches from our group at Purdue University on the USP in the aspects of modelling the kinetics of the shots, predicting the surface topography of the peened samples and producing the nanostructured grains on the solid metals and alloys. Research results suggest that finite element method and the developed calculation algorithm can be used for the surface morphology prediction and the USP is capable of surface nanocrystallisation and grain refinement on solid metals. For instance, the topic of the biological enhancement for metallic bio-implant materials via the USP was discussed as well according to our preliminary investigations. The related researches in these topics are discussed and some possible addresses for future study in these fields are drawn and underlined.